Interaction between human leukocyte antigen (HLA-C) and killer cell Ig-like receptors (KIR2DL) inhibits the cytotoxicity of natural killer cells in patients with hepatoblastoma - Guo, Jing-Jie; Ye, Yong-Qin; Liu, Yi-Di; Wu, Wei-Fang; Mei, Qian-Qian; Zhang, Xi-Yun; Lao, Jing; Wang, Bin; Wang, Jian-Yao (Frontiers in Medicine, 2022)
Background: Hepatoblastoma (HB) is the most common liver malignancy in childhood with poor prognosis and lack of effective therapeutic targets. Single-cell transcriptome sequencing technology has been widely used in the study of malignant tumors, which can understand the tumor microenvironment and tumor heterogeneity. Methods: Two children with HB and a healthy child were selected as the research subjects. Peripheral blood and tumor tissue were collected for single-cell transcriptome sequencing, and the sequencing data were compared and analyzed to describe the differences in the immune microenvironment between children with HB and normal children. Results: There were significant differences in the number and gene expression levels of natural killer cells (NK cells) between children with HB and normal children. More natural killer cells were seen in children with HB compared to normal control. KIR2DL were highly expressed in children with HB. Conclusion: Single-cell transcriptome sequencing of peripheral blood mononuclear cells (PBMC) and tumor tissue from children with HB revealed that KIR2DL was significantly up-regulated in NK cells from children with HB. HLA-C molecules on the surface of tumor cells interact with inhibitory receptor KIR2DL on the surface of NK cells, inhibiting the cytotoxicity of NK cells, resulting in immune escape of tumors. Inhibitors of related immune checkpoints to block the interaction between HLA-C and KIR2DL and enhance the cytotoxicity of NK cells, which may be a new strategy for HB treatment.